Acknowledgement to Reviewers 2020-2021 - Gabinete editorial, Revista Portuguesa de Investigação Comportamental e Social (2021)
The high scientific standards maintained by the Portuguese Journal of Behavioral and Social Research in its papers owe much to the effort of the reviewers, who gave their time and knowledge freely. Thus, the Editors of the Portuguese Journal of Behavioral and Social Research acknowledge with particular gratitude the following reviewers who have reviewed papers during the period November 2020–November 2021.